The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s10508-016-0857-5
|View full text |Cite|
|
Sign up to set email alerts
|

The Diversity and Prevalence of Sexual Orientation Self-Labels in a New Zealand National Sample

Abstract: In this study, we asked participants to "describe their sexual orientation" in an open-ended measure of self-generated sexual orientation. The question was included as part of the New Zealand Attitudes and Values Study (N = 18,261) 2013/2014 wave, a national probability survey conducted shortly after the first legal same-sex marriages in New Zealand. We present a two-level classification scheme to address questions about the prevalence of, and demographic differences between, sexual orientations. At the most d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 37 publications
3
22
1
Order By: Relevance
“…Participants who selected the latter option subsequently went on to identify with a range of different terms, with nonbinary, agender, and genderqueer being the three most popular. Likewise, in their New Zealand national probability sample, Greaves et al (2017Greaves et al ( , 2421 pointed to a correlation between asexual identification and non-cisgender identification (although they do not disaggregate this category).…”
Section: (A)sexuality and Gendermentioning
confidence: 98%
“…Participants who selected the latter option subsequently went on to identify with a range of different terms, with nonbinary, agender, and genderqueer being the three most popular. Likewise, in their New Zealand national probability sample, Greaves et al (2017Greaves et al ( , 2421 pointed to a correlation between asexual identification and non-cisgender identification (although they do not disaggregate this category).…”
Section: (A)sexuality and Gendermentioning
confidence: 98%
“…In terms of prevalence of sexual minorities, Greaves et al (2017) reported that out of a large national sample of more than 18,000 New Zealanders, 2.6% described their sexual orientation as lesbian/gay, with another 1.8% bisexual. However, the researchers used a novel approach to gather this data, offering the question of sexual orientation as an open-ended item.…”
Section: The New Zealand Contextmentioning
confidence: 99%
“…“What is your gender?”) from the sixth wave (2014/2015) and were coded as men, women, transgender, nonbinary, unsure, or outside the scope. Our need to maximize potential matches meant only those coded as men or women were included in the model (0.3% of participants in the NZAVS identify as gender diverse; Greaves et al, 2017). Participants were asked which ethnic group they identify with; analyses included codes for the minority groups “Māori” (0 = no, 1 = yes), “Pasifika” (0 = no, 1 = yes), and “Asian” (0 = no, 1 = yes) with the reference group representing the NZ Pakeha/European majority.…”
Section: The Current Researchmentioning
confidence: 99%